Psychospołeczne podstawy tworzenia ustaw o ochronie przeciwpożarowej i Państwowej Straży Pożarowej - Cenin, Mieczysław (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article contains apresentation of the author’s academic and implementation work in the years 1986–2016 in the scope of interdisciplinary actions of the Lower Silesian Project Team featuring representatives of Lower Silesian firefighters and academic employees of the Wrocław University, whose objective was to create alegislative basis for thorough reform of the fire service in Poland. The basis for such activity were results of own academic research encompassing the topic of the effectiveness of psychological methods essential to persons performing difficult and hazardous tasks conducted under the Interkosmos program. In further sections of this article the author discusses the various functions he has held in the Project Team. He presents acharacteristic of the System of Psychological Support of Rescue Services project, put into practice to prevent and combat the effects of post-traumatic stress within the fire service, as an impetus for the practical execution of the implemented laws.Additionally, the article features acondensed, yet thorough psychological analysis of the motivational side of the firefighters’ pro-reform activity, which unveils valuable sources of the firefighters’ spirit and its causative power.
Keywords: Państwowa Straż Pożarna; ochrona przeciwpożarowa; tworzenie prawa; podstawy psychologiczne